COMPARISON OF THE RESPONSIBILITY TO EXTRACT AND PURIFY β -GLUCAN OF SOME CEREAL GRAINS FOR SPECIFIC METHOD - Karim, H. S.; Zainulabidden, M. W.; Sabir, D. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The current study prioritized certain popular local cereal species like Wheat, Oat, Rye and two local Barley varieties known as Aksad and Amal to extract their β- glucan using alchemical methods. The results of this study indicated that rye contained the lower percentage of β-glucans (0.756%) whereas, both types of barley Aksad and Amal contained highest amount (9.489%) and (7.395%) respectively. However, the results showed that the crude extracted of β- glucans from wheat, oat, rye, barley (Aksad) and barley (Amal) were 0.373,1.409, 0.26, 2.287 and 1.855 g/100g flour respectively which was reflected the efficiency of extraction process which ranged between 8.83 ± 0.01for wheat to 34.39 ± 0.02 for rye, the precipitating by ammonium sulfate were useful for purifying of oat and barley β- glucan which their purity increased to about 10- 15% to reach their purity to 84.88 for barley (Amal) to 95.18% for oat. All the bands of Ft-IR Spectra showed to take place absorbance at these regions by β- glucan are present in the all scanned studied samples with some differences in their areas and absorbance. A robust and sharp peak at 1304.37 cm-1 appeared only with the control sample while it is absent in the studied β-glucan. Results of HPLC illustrated that all purified cereal β- glucan appeared only one peak at the same Retention time RT of standard oat β- glucan which ranged between 17.429 to 17.453 min.